Temperature effect on seed germination in Canna indica L. (Cannaceae) - Souza, P. R.M. [UNESP]; Tozzi, H. H. [UNESP]; Takaki, M. [UNESP] (International Seed Testing Association, 2011)
Canna indica L. is an herbaceous species with ornamental and medicinal value, having seeds with a hard seed coat. This study aimed to test the influence of constant temperatures ranging from 5 to 45°C, at 5°C intervals, on the germination of scarified seeds. Data obtained were analyzed through the model of enthalpy of activation in order to obtain the optimum temperature range for germination. The species showed seed germinability in a wide temperature range (10-40°C) being the optimal temperature range between 13.84 and 34.41°C, determined by the enthalpy of activation.